Atherosclerosis: From the Disruption of Mitochondrial Membrane Potential to the Potential Interventional Strategies - Xia, Dexiang; Chen, Yanmei; Luo, Guifang; Wei, Dangheng (Current medicinal chemistry, 2023)
Atherosclerosis (AS) is the major factor of cardiovascular disease (CVD) and is characterized by a progressive and chronic inflammatory process in the arterial wall. Recent studies have shown that disruption of the mitochondrial membrane potential (deltapsi (m)) directly affects the electron transport chain (ETC), which in turn leads to oxidative stress, and furthermore, its alteration leads to apoptosis and activation of the NLRP3 inflammasome, thereby promoting the development of AS. Here, this review describes how deltapsi (m) contributes to the development of AS by mediating oxidative stress, apoptosis, and NLRP3 inflammasome activation, and potential AS intervention strategies by targeting oxidative stress, apoptosis, and NLRP3 inflammasome activation induced by deltapsi (m).